Does Cigarette Smoke Exposure on Pregnant Women Increase The Risk of Autism Spectrum Disorders in Their Children? - Nani, Desiyani (Jurnal Keperawatan Soedirman, 2022)
The prevalence of autism spectrum disorder (ASD) has increased over the last three decades. Although genetic factors have a big contribution to ASD, environmental factors, prenatal, and postnatal factors were also found to be related. According to past literature, exposure to cigarette smoke during pregnancy raises the risk of behavioral problems in children, including ASD. The purpose of this study was to determine the relationship between maternal exposure to cigarettes during pregnancy and the risk of having a child with ASD in Indonesia. This is a case-control study that was conducted in Banyumas, Indonesia. The study consisted of 47 children with ASD as the case group and 195 healthy children as the control group. The Chi-Square test was used to evaluate the relationship between exposure to cigarettes and ASD. The findings showed that exposure to cigarette smoke from active or passive smokers during pregnancy was associated with the occurrence of ASD in children (p < 0.05). Exposure to cigarette smoke during pregnancy raises the risk of ASD in children. Therefore, nurses should provide adequate education to the community about the dangers of exposure to cigarette smoke during pregnancy and the risks for ASD in their children.